Impact of varying analytical methodologies on grain particle size determination - Kalivoda, Julie R.; Jones, Cassandra K.; Stark, Charles R. (My University, 2017)
The determination of particle size is an important quality control measurement for feed manufacturers, nutritionists, and producers. The current approved method for determining the geometric mean diameter by weight (d(gw)) and geometric standard deviation (S-gw) of grains is standard ANSI/ASAE S319.4. This method controls many variables, including the suggested quantity of initial material and the type, number, and size of sieves. However, the method allows for variations in sieving time, sieve agitators, and the use of a dispersion agent. The objective of this experiment was to determine which method of particle size analysis best estimated the particle size of various cereal grain types. Eighteen samples of either corn, sorghum, or wheat were ground and analyzed using different variations of the approved method. Treatments were arranged in a 5 x 3 factorial arrangement with 5 sieving methods: 1) 10-min sieving time with sieve agitators and no dispersion agent, 2) 10-min sieving time with sieve agitators and dispersion agent, 3) 15-min sieving time with no sieve agitators or dispersion agent, 4) 15-min sieving time with sieve agitators and no dispersion agent, and 5) 15-min sieving time with sieve agitators and dispersion agent conducted in 3 grain types (ground corn, sorghum, and wheat) with 4 replicates per treatment. The analytical method that resulted in the lowest dgw and greatest Sgw was considered desirable because it was presumably representative of increased movement of particles to their appropriate sieve. Analytical method affected dgw and Sgw (P <= 0.05) measured by both standards. Inclusion of sieve agitators and dispersion agent in the sieve stack resulted in the lowest dgw, regardless of sieving time. Inclusion of dispersion agent reduced dgw (P <= 0.05) by 32 and 36 mu m when shaken for 10 and 15 min, respectively, compared to the same sample analyzed without dispersion agent. The addition of the dispersion agent also increased S-gw. The dispersion agent increased the quantity of very fine particles collected in the pan; therefore, S-gw was significantly greater (P <= 0.05). Corn and sorghum ground using the same mill parameters had similar dgw (P > 0.05), but wheat ground using the same mill parameters was 120 to 104 m larger (P = 0.05) than corn and sorghum, respectively. Both sieve agitators and dispersion agent should be included when conducting particle size analysis. The results indicate that 10 and 15 min of sieving time produced similar results.
Citation: Kalivoda, J. R., Jones, C. K., & Stark, C. R. (2017). Impact of varying analytical methodologies on grain particle size determination. Journal of Animal Science, 95(1), 113-119. doi:10.2527/jas2016.0966
Keywords: Feed; Grain; Methodology; Particle Size Analysis; Broiler Live Performance; Finishing Pigs